Experimental Study of Laser-Induced Brass and Copper Plasma for Spectroscopic Applications. (20th June 2012) - Gojani, Ardian B.
Abstract : This paper presents time-resolved and space-integrated laser-induced breakdown spectroscopic (LIBS) analysis of copper and brass plasma. It was observed that copper emission is very strong during the first hundred nanoseconds of the plasma, but then some lines (e.g., at 327.4 nm) decrease in intensity, while others (e.g., 521.8 nm) slightly increase. Zinc lines, on the other hand, did not decrease significantly in intensity even two microseconds after ablation, but they became narrower due to the decrease of the density of free electrons. Copper line intensities showed the same characteristics regardless whether the plasma was created in a metallic copper or brass sample. Assuming local thermodynamic equilibrium, plasma temperature, and electron density is obtained from Boltzmann plot and Lorentzian profile fitting, respectively. The effect of subsequent irradiation on the same spot was investigated, and the number of necessary shots for surface cleaning was determined.